Would you tell me, please, which way I ought to go from here?” “That depends a good deal on where you want to get to,” said the Cat. “I don’t much care where—” said Alice. “Then it doesn’t matter which way you go,” said the Cat.“—so long as I get somewhere,” Alice added as an explanation. “Oh, you’re sure to do that,” said the Cat, “if you only walk long enough", Alice in Wonderland, Lewis Carroll.
A group is called Abelian if ab = ba ∀a, b ∈ G. Every group of prime order (every group of prime order is cyclic), order five or smaller, or cyclic is Abelian. $\mathbb{S}_3$ is the smallest non-commutative group.
Cauchy’s Theorem for Abelian Groups. Lemma 1. If p prime divides the order of a finite Abelian group G, then G has an element of order p.
Lemma 2. G is a finite Abelian p-group if and only if its order is a power of p (|G| = pn for some positive integer n).
Lemma 3. Let G be a finite Abelian group, and let m = |G| = p1r1p2r2···pkrk where p1, p2, ···, pk are distinct primes that divide m. Then, G is an internal direct product of cyclic groups of prime-power order, that is, G ≋ G1 x G2 x···x Gk with |Gi| = piri
The Fundamental Theorem of Finite Abelian Groups. Every finite Abelian group G is the direct sum of cyclic groups, each of prime power order.
If G is a cyclic group of order n ⇒ G ≋ ℤn. Therefore, the Fundamental Theorem of Finite Abelian Groups states that every finite Abelian group is isomorphic to ℤp1n1⊕ℤp2n2⊕···⊕ℤpknk where the pi’s are not necessarily distinct primes. Moreover, the list of prime powers appearing {p1n1, p2n2, ···, pknk} is unique, up to re-ordering.
Lemma 4. Let G be a finite Abelian p-group (a prime-power order group) and let g be an element of maximal order in G. Then, G can be written in the form ⟨g⟩ x K for some K ≤ G, G ≋ ⟨g⟩ x K.
Proof.
We denote |G| = pn and induct on n.
Base Case. If n = 1, then |G| = p, p prime ⇒[All groups of prime order are cyclic groups and they are isomorphic to ℤp] ℤp ≋[G is cyclic ⇒ ∃g ∈ G: G = ⟨g⟩] ⟨g⟩ x {e}
Induction Hypothesis. Suppose ∀m, 1 ≤ m < n, the result holds for all groups of order pm, and |G| = pn and let g ∈ G such that ord(g) is maximal.
In other words, among all the elements of G, choose “g” of maximal order, |g| = ord(p) = pk.
Since the order of an element divides the order of a group, p is prime, and therefore ord(g) = pk where k is some integer as large as possible, but obviously it could never be bigger than n.
Since the order of an element divides the order of a group, p is prime, and therefore ord(h) = pr and pr ≤ pk ↭ r ≤ k and that’s the case because g is an element of maximal order in G and ord(g) = pk ⇒ ord(hp) =[$|⟨a^k⟩|=\frac{n}{gcd(n, k)}$] pr/gcd(pr, p) = pr/p = pr-1 < ord(h) = pr ⇒[By the minimality of h] hp ∈ ⟨g⟩ ⇒ ∃a ∈ ℤ such that hp = ga.
$(g^a)^{p^{k-1}} = (h^p)^{p^{k-1}} = h^{p^k}$ = [ord(h) = pr, r ≤ k] e ⇒ $(g^a)^{p^{k-1}} =e$ ⇒ ord(ga) ≤ pk-1 ⇒[g ∈ G has order pk maximal, ord(ga) = $\frac{ord(g)}{gcd(ord(g),a)}$. If gcd(ord(g), a) = 1, then ord(ga) = ord(g)⊥ ord(g) = pk and ord(ga) ≤ pk-1] gcd(ord(g), a) ≠ 1, that is, gcd(pk, a) ≠ 1, and p prime ⇒ p | a ⇒ ∃s∈ ℤ: a = ps ⇒ hp = ga = gps ⇒ hp = gps ⇒ (gps)-1hp = e ⇒ (g-s)php = e ⇒ (g-sh)p = e.
Let’s consider this recently constructed element x = g-sh, x ≠ e (x = e ⇒ g-sh = e ⇒ h = gs ∈ ⟨g⟩ ⊥), and xp = e. Since p prime, |G| = pn, x ≠ e, xp = e ⇒ ord(x) = p. Besides, x ∉ ⟨g⟩ because otherwise, x = g-sh = gt for some t ⇒ h = gs+t∈ ⟨g⟩⊥] Therefore, by the minimality of order of h, ord(h) = p (x ∉ ⟨g⟩, ord(x) = p, G is a finite Abelian p-group).
Let’s study the intersection ⟨g⟩ ∩ ⟨h⟩, ∀y ∈ ⟨g⟩ ∩ ⟨h⟩ ⇒ [ord(h)=p ⇒ ⟨h⟩ = {e, h, h2, ···, hp-1}] ∃a∈ ℤ: y = ha, 0 ≤ a ≤ p-1.
If a ≠ 0 ⇒[p prime, 0 < a ≤ p-1] gcd(a, p) = 1 ⇒[Bezout’s identity] ∃r, s∈ ℤ: ar + ps = 1 ⇒ yr = $h^{a^r}=h^{ar} = h^{1-ps}=h·(h^p)^{-s}$ =[ord(h)=p ⇒hp = e] h. Consider ∀y ∈ ⟨g⟩ ∩ ⟨h⟩ ⇒[Intersection of two subgroups of a group is again a subgroup] yr = h ∈ ⟨g⟩ ∩ ⟨h⟩ ⇒ h ∈ ⟨g⟩⊥ ⇒ a = 0 ⇒ y = ha = h0 = e, that is, ∀y ∈ ⟨g⟩ ∩ ⟨h⟩, y = e ⇒ ⟨g⟩ ∩ ⟨h⟩ = {e}.
Set H = ⟨h⟩, consider the coset gH ∈ G/H (|G/H| = $\frac{p^n}{p} = p^{n-1}$), and let’s calculate the order of gH. Set r = ord(gH), r = ord(gH) | ord(g) 💡. Futhermore, grH = (gH)r = eH ⇒[aH = bH ↭ a ∈ bH] gr ∈ H ⇒ gr ∈ ⟨g⟩ ∩ ⟨h⟩ = {e} ⇒ gr = e ⇒ ord(g) | r ⇒ [We have previously stated that r | ord(g)] r = ord(g) = ord(gH) = pk.
💡Order of Coset in Quotient group divides order of element. Suppose ord(g) = m ⇒ gm = e. (gH)m = gmH = eH = H, which is the identity of G/H ⇒ ord(gH) ≤ m. Hence, m is one positive integer with (gH)m, but there may be smaller ones.
Since m ≥ n = ord(gH) ⇒ m = qn + r, 0 ≤ r < n. H = (gH)m = (gH)qn+r = (gH)qn(gH)r = ((gH)n)q(gH)r =[H is the identity on the quotient group G/H, that is, G/H under the multiplication of cosets] H(gH)r = (gH)r.
If r ≠ 0 ⊥ because ord(gH) = n, r < n ⇒ r = 0 ⇒ m = qn ⇒ n | m
Therefore, ord(gH) = pk and this is maximal because ∀x ∈ G, ord(xH) | ord(x) and by construction, g has maximal order (|g| = pk), so we can apply the induction hypothesis to G/H because |G/H| = $\frac{p^n}{p} = p^{n-1}$ < pn = |G|, the original group where ⟨gH⟩ is maximal ⇒[The Fourth Isomorphism Theorem. Let N ◁ G. There is a 1–1 correspondence between subgroups of G/N and subgroups of G that contain N. In particular, every subgroup of G/N has the form A/N for some A satisfying N ≤ A ≤ G] G/H ≋ ⟨gH⟩ x K/H, H ≤ K ≤ G.
Claim: G ≋ ⟨g⟩ x K.
The Fundamental Theorem of Finite Abelian Groups. Every finite Abelian group G is the direct sum of cyclic groups, each of prime power order. |G| = n = p1r1p2r2···pkrk. Then,
The number of terms in the direct product, as well as the order of the cyclic groups, are uniquely determined by the group.
Proof.
By Lemma 3, [Let G be a finite Abelian group, and let m = |G| = p1r1p2r2···pkrk where p1, p2, ···, pk are distinct primes that divide m. Then, G is an internal direct product of cyclic groups of prime-power order, that is, G ≋ G1 x G2 x···x Gk with |Gi| = piri] G ≋ G1 x G2 x ··· Gi where p1, p2,···, pk are distinct primes that divide m, |Gi| = piri.
By Lemma 4, each Gi can be written in the form ⟨gi⟩ x Hi for some Hi ≤ Gi ⇒[⟨gi⟩ ≋ ℤpisi] Gi ≋ ℤpisi x Hi, and we proceed by induction on Hi, and we will end up on the desired result ℤpin1⊕ℤpin2⊕···⊕ℤpink, n1 + n2 + ··· + nk = ri ∎